2016
DOI: 10.21786/bbrc/9.1/9
|View full text |Cite
|
Sign up to set email alerts
|

Design and in silico analysis of pentavalent chimeric antigen against three enteropathogenic bacteria: enterotoxigenic E. coli, enterohemorragic E. coli and Shigella

Abstract: Coronaviruses such as SARS-CoV had caused high fatalness around the globe and have been a terror for public health, crafting a need for effective and active vaccines and drugs. Although this virus, coronavirus causing respiratory syndrome was controlled by non-vaccinated trials and measuresprimarily, still it persisted to be the leading threat for human health. Therefore thestrategy of optimal SAR-CoV drugs and vaccines is a priority, at present. Such drugs and vaccines represent key challenges: the immunity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, geographically the prevalence is so variable. For example, the bacterial diarrhea caused by Shigella in different cities has been as follow: Zanjan 19.6 %, 22 Ahvaz 14.1 %, 23 Kerman 31.6%, 12 Shahr-e-Kord 7.8%, 24 and Kashan 7.8%. 25 In Tehran, in a study by Afshari et al in summer and autumn of 2012, it was shown that 5.3% of diarrheal cases are caused by Shigella, 21 and Dolatshahi et al, in another study in a period of 10 months from April to January 2015, showed that this rate was 5.16%.…”
Section: Discussionmentioning
confidence: 99%
“…However, geographically the prevalence is so variable. For example, the bacterial diarrhea caused by Shigella in different cities has been as follow: Zanjan 19.6 %, 22 Ahvaz 14.1 %, 23 Kerman 31.6%, 12 Shahr-e-Kord 7.8%, 24 and Kashan 7.8%. 25 In Tehran, in a study by Afshari et al in summer and autumn of 2012, it was shown that 5.3% of diarrheal cases are caused by Shigella, 21 and Dolatshahi et al, in another study in a period of 10 months from April to January 2015, showed that this rate was 5.16%.…”
Section: Discussionmentioning
confidence: 99%
“…CAI of the optimized gene was changed from 0.64 to 0.91. Generally, the lower the CAI number of a gene, the poorer expression of that gene ( 25 ). In the original sequence, ENC, which reflects the presence of the different codon types in a sequence, was 33, while after the codon-optimization, with the deletion of the rare codons, it reached to 20.…”
Section: Discussionmentioning
confidence: 99%
“…Although, currently there is no approved human vaccine against the bacteria, many studies have identified some potent antigens, which the antibody against them will be increased in naturally infected patients [24,25], and, therefore, they are good choices for developing an efficient subunit vaccine. In this regard, the immune responses to St  1, St  2, lipopolysaccharide (LPS), and locus of enterocyte attachment and effacement (LEE)-encoded proteins, mainly Tir, intimin, EspA, and EspB, have been examined in many studies [26][27][28].…”
Section: Introductionmentioning
confidence: 99%